ADVANCE HYDRAULIC SUPPORT MULTI-OBJECTIVE OPTIMIZATION DESIGN BASED ON NSGA-Ⅱ ALGORITHM - NIU YanQi; LIU Wei; ZHANG DeSheng (Jixie qiangdu)
Contrapose the problems of hydraulic support connecting rod mechanical fracture,at the same external load force link mechanical to advance the sum of the absolute values,and minimum quality of the objective function,establishment of a multi-objective optimization model,to solve the optimization used the NSGA-Ⅱ algorithm,using fuzzy set theory method to choose the optimal solution,and has compiled into a visual computing program under matlab environment. This program applications optimized ZTC16044 /27 /50 advanced hydraulic support arguments,after optimization the length reduce 29. 28 kg,the maximum force reduce 349. 12 k N. ZTC16044 /27 /50 link mechanical fracture coal mine accident did not occur in continuous operation Hong Liu-lin,to improve the overall performance of advanced hydraulic support provides an effective way.